Pengaruh Ukuran Bulbil terhadap Pertumbuhan Bibit Tanaman Porang (Amorphophallus oncophyllus Prain) - Marlina Marlina; Salsabila Ramadhani; Indah Rahma Dewi; Ahmad Aufa Yamani; Anggi Amelia; Eka Safitri (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Marlina M, Ramadhani S, Dewi IR, Yamani AA, Amelia A, Safitri E. 2021. Effect of bulbil size on growth of porang (Amorphophallus oncophyllus Prain) nursery. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 755-762. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Porang (Amorphophallus sp.) was perennial crops belongs to the genus Amorphophallus, family Araceae. The glukomanan in Porang plant (Amorphophallus konjac. Koch) was potential on many aspects such of nutrition, included of fungsional food,additive food and also it’s derivate.To prepare the plant material for propagation need the qualified and similar in bulbils size of Porang plant. The aim of the research was find out the response growth of various bulbil weight size. The experiment was organized by completely random designed.The units experiment where each type of bulbil were grown with 3 replications. Each unit experiment consisted of 24 bulbils. The treatments were average weight size of each bulbils, that were A. 9,69 g/bulbil, B. 10,74 g/bulbil, dan C. 12,98 g/bulbil.The ANOVA test was applied to all data.The result showed that differences in bulbils average weight size significantly affected the germination percentage and the shoot height of porang plants, but not significantly affected the rate of germination and also the sum of shoot leaflets. The best results for all parameter were given by bulbils derived from 10,74 g/bulbil on average weight size of bulbils and no significant with 9,69 g/bulbil, thats were responsed in high germination percentage (58% to 86%) for 4 weeks seedling bed and also in shoots height (32 cm to 42,8cm) of 4 weeks polibag nursery with leaftlets amount in range of 7,7 to 10,7 sheets/plant. As the conclusion of the weigth size of bulbils was that light weight size resulted high germination percentage and also shoot height of Porang plant. Dormancy was affected of weight size of bulbils, that was indicated in low germination response of heavy one of bulbils.